Renovascular Hypertension Due to Midaortic Syndrome Associated with Chronic Takayasu Arteritis Successfully Treated with Multiple Simultaneous Visceral Bypasses - Hyokee Kim; Ahram Han (Vascular Specialist International, 2021)
Aortoiliac occlusive disease may limit the use of branched endovascular aneurysm repair (BEVAR) of thoracoabdominal aneurysms (TAAAs). Thus, infrarenal aortoiliac occlusion may preclude the use of BEVAR. We present a case involving a 67-year-old patient with a fast-progressing TAAA (diameter: 70 mm) and a concomitant total aortoiliac occlusion. A multi-staged treatment concept included the creation of the access and the distal landing zone for the consecutive endovascular procedures through an aorto-right femoral-left popliteal bypass. At six-week intervals, thoracic endovascular aortic repair for the creation of the proximal landing zone and a 4-vessel BEVAR were accomplished. At 36 months, a type III endoleak occurred due to the fracture of the bridging stent-graft to the celiac trunk and the superior mesenteric artery. It was successfully treated with VBX stent-grafts. This case illustrates the importance of a staged hybrid approach in the management of complex aortic pathologies with poor access and insufficient distal landing zone.